2007
DOI: 10.1016/j.jneuroim.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

A vitamin A deficient diet enhances proinflammatory cytokine, Mu opioid receptor, and HIV-1 expression in the HIV-1 transgenic rat☆

Abstract: The HIV-1 (HIV) transgenic (Tg) rat develops several immune abnormalities in association with clinical impairments that are similar to what are seen with HIV infection in humans. In HIV infection, retinoids and opioids can have separate and potentially combined effects on the clinical course of HIV disease. In these studies, the effects of a vitamin A deficient diet on T cell proinflammatory cytokine and mu opioid receptor (MOR) expression were examined in the Tg and in wild-type (WT) rats. The effects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…This model is, however, ideal for investigating the efficacy of therapeutic treatments which reduce neurological dysfunction in HIV-infected individuals in the post-cART era. The use of this rodent model for investigating neurologically related issues has been well established (Royal, Wang et al 2007; Kass and Chang 2010; Moran, Aksenov et al 2012; Royal, Zhang et al 2012). Moran and colleagues (2012, 2013) used this model to test alterations in sensorimotor gating and behavior resulting from HIV-1 infection, including changes in dopamine (DA) function (Moran, Aksenov et al 2012; Moran 2013).…”
Section: The Hiv-1tg Rat As a Model Of Neurohivmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is, however, ideal for investigating the efficacy of therapeutic treatments which reduce neurological dysfunction in HIV-infected individuals in the post-cART era. The use of this rodent model for investigating neurologically related issues has been well established (Royal, Wang et al 2007; Kass and Chang 2010; Moran, Aksenov et al 2012; Royal, Zhang et al 2012). Moran and colleagues (2012, 2013) used this model to test alterations in sensorimotor gating and behavior resulting from HIV-1 infection, including changes in dopamine (DA) function (Moran, Aksenov et al 2012; Moran 2013).…”
Section: The Hiv-1tg Rat As a Model Of Neurohivmentioning
confidence: 99%
“…Moran and colleagues (2012, 2013) used this model to test alterations in sensorimotor gating and behavior resulting from HIV-1 infection, including changes in dopamine (DA) function (Moran, Aksenov et al 2012; Moran 2013). Royal et al (2007, 2012) used the HIV-1Tg rat to test the effects of vitamin A deficiency on HIV-1-associated neuroinflammation and mu opioid receptor (MOR) expression as well as peripheral and CNS immune responses in HIV infection (Royal, Wang et al 2007; Royal 2012). Rao et al (2011) found that HIV-1Tg rats exhibit neurological markers for neuroinflammation that are associated with cognitive impairment, and they identified neuroinflammation as a target for treatment of such impairment in HIV-positive populations (Rao, Kim et al 2011).…”
Section: The Hiv-1tg Rat As a Model Of Neurohivmentioning
confidence: 99%
“…In studies of vitamin A deficiency using the transgenic rat, T cells from deficient animals produced higher levels of IFN-γ and secreted increased amounts of TNF-α than what was observed for non-deficient rats [64]. In addition, transgenic rats with vitamin A deficiency produced higher levels of MOR mRNA than non-deficient rats and wild type rats on either diet.…”
Section: The Transgenic Rat Model Of Hiv Infectionmentioning
confidence: 89%
“…It is an ideal model for investigating the efficacy of therapeutic treatments which reduce neurological dysfunction in HIV-infected individuals in the post-HAART era. The use of this rodent model for investigating neurologically related issues has been well established Moran, Aksenov, Booze, Webb, & Mactutus, 2012;Moran, Booze, Webb, & Mactutus, 2013;Royal, Wang, Jones, Tran, & Bryant, 2007;Royal et al, 2012). For example, Moran et al (2012Moran et al ( , 2013 used this model to test alterations in sensorimotor gating and behavior resulting from HIV-1 infection, including changes in dopamine (DA) function.…”
Section: Brain-immune Interactions: Induction Of Neuroinflammation Bymentioning
confidence: 99%
“…For example, Moran et al (2012Moran et al ( , 2013 used this model to test alterations in sensorimotor gating and behavior resulting from HIV-1 infection, including changes in dopamine (DA) function. Royal et al (2007Royal et al ( , 2012 used the HIV-1Tg rat to test the effects of vitamin A deficiency on HIV-1-associated neuroinflammation and mu opioid receptor (MOR) expression as well as peripheral and CNS immune responses in HIV infection. Also, Rao et al (2011) found that HIV1Tg rats exhibit neurological markers for neuroinflammation which are associated with cognitive impairment and identified neuroinflammation as a target for improving such impairments in HIV-positive populations (Rao et al, 2011).…”
Section: Brain-immune Interactions: Induction Of Neuroinflammation Bymentioning
confidence: 99%